Cuticle of 'Gala' and 'Galaxy' apples cultivars under different environmental conditions - Magda Andréia Tessmer; Lucimara Rogéria Antoniolli; Beatriz Appezzato-da-Glória (Brazilian Archives of Biology and Technology, 2012)
This study aimed to analyze the cuticle thickness and pattern of epicuticular wax deposition in 'Gala' and 'Galaxy' apple cultivars (Malus domestica Borkh,) from three Brazilian producing areas: Vacaria (RS), Fraiburgo (SC) and São Joaquim (SC) with altitudes of 971, 1,048 and 1,353m, respectively. Harvested fruit were kept under two storage conditions: regular atmosphere (RA) (0 ºC and 90% RH) and controlled atmosphere (CA) (1.5% O2, 2.5% CO2, 0ºC and 90% RH). Cuticle thickness measurements were made using LM and the deposition pattern of epicuticular wax observed with a SEM. Altitude among the apple producing areas was not a factor in deposition pattern of waxes between the cultivars but at higher altitudes, the cuticle was thicker in both the cultivars. In the freshly-harvested fruits, waxes deposition in the form of platelets and the mechanism of “tear and repair” were observed. Severity of microcracks in the cuticle was more evident on the fruits from CA.